(Dis)Satisfaction of users: duplication and simulataneous use of services in Family Health - Mishima, Silvana Martins; Paula, Vanessa Garcia de; Pereira, Maria José Bistafa; Almeida, Maria Cecília Puntel de; Kawata, Lauren Suemi (Revista da Escola de Enfermagem da USP, 2010)
This descriptive and exploratory study was performed with the purpose to identify the pattern of use of health services: duplication and simultaneous use in a District Reference Unit (URD, acronym in Portuguese) and four Family Health Units (USF, acronym in Portuguese). Secondary data were collected in two stages: the first stage involved identifying the Service Files of the District Reference Unit for 15 days of the month of June 2006; and the second stage involved verifying 856 services delivered among the selected USF to users who were seen at the URD. It was found that there was duplication in the use of health services corresponding to 0.35% of the users seen at the group of services, as well as simultaneous use, corresponding to 3.27% of users. The duplication of health service use is considered to be an indirect indicator for the analysis of user satisfaction, i.e., service use duplication may be understood as an expression of user dissatisfaction.